The Phenomenon of Shift (Hijrah) in Pesantren Colleges (A Social and Political Study) - Aini, Nur Lathifah; Majid, Ach. Nurholis (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2024)
How Hijrah is intensified as a contemporary fashion trend, but this is very contrary to its meaning in terms of religion. Automatically, the impact caused leads to hijrah limited to life style, not to actual practice.Therefore, pesantren colleges are present as a breakthrough educational institution that takes a role to restore the essential meaning of hijrah. The study in this article focuses on how this shift (hijrah) occurs in pesantren colleges and how identity politics is carried out there. Using qualitative approaches and case study types researchers, data collected by interviews, observations and documentation. After the data is collected, researchers then analyze the data interactively. Checking the validity of data is done by triangulation of sources and techniques. This research result show the fact that the phenomenon of hijrah displayed in pesantren colleges purely comes from the students by being described into three classifications, namely: 1) Hijrah in the nuances of pesantren colleges; 2) Hijrahh narrative as a reference for action; and 3) Actualization of the meaning of hijrah among students.Ketika Hijrah digencarkan beririsan dengan tren fashion saat ini, yang terjadi hal ini sangat bertolak belakang dengan maknanya dari segi agama. Secara otomatis, dampak yang ditimbulkan mengarah pada hijrah sebatas gaya hidup, bukan pada praktik yang sesungguhnya. Kaitan dengan ini, pesantren bisa hadir sebagai lembaga pendidikan yang mengambil peranan untuk mengembalikan makna esensial dari hijrah. Kajian dalam artikel ini berfokus pada bagaimana pergeseran (hijrah) ini terjadi di pesantren dan bagaimana politik identitas dan bagaimana politik identitas dapat disemai di sana. Dengan menggunakan pendekatan kualitatif dan jenis penelitian studi kasus, dengan data yang dikumpulkan melalui wawancara, observasi dan dokumentasi. Setelah data terkumpul, peneliti kemudian menganalisis data secara interaktif. Pengecekan keabsahan data dilakukan dengan cara triangulasi baik sumber maupun teknik. Berdasarkan hasil penelitian diperoleh fakta bahwa fenomena hijrah yang ditampilkan di pesantren yang murni berasal dari para santri, bisa diklasifikasikan ke dalam tiga bentuk, yaitu: 1) Hijrah dalam nuansa pesantren; 2) Narasi hijrah sebagai acuan untuk bertindak; dan 3) Aktualisasi makna hijrah di kalangan santri.